2017
DOI: 10.1002/2016gl071020
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of waves, tides, and nontidal residuals to extreme total water levels on U.S. West Coast sandy beaches

Abstract: To better understand how individual processes combine to cause flooding and erosion events, we investigate the relative contribution of tides, waves, and nontidal residuals to extreme total water levels (TWLs) at the shoreline of U.S. West Coast sandy beaches. Extreme TWLs, defined as the observed annual maximum event and the simulated 100 year return level event, peak in Washington, and are on average larger in Washington and Oregon than in California. The relative contribution of wave‐induced and still water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 51 publications
6
98
0
Order By: Relevance
“…The direct simulation of extreme compound TWL events also allows for a greater investigation of the respective constitutive components. Similar to the findings of Serafin et al (), Figure demonstrates how annual maxima can occur across a broad range of values within each TWL component. Identifying the 1% recurrence events (red dots in Figure , defined as the fifth largest event in each simulation) reveals the degree to which this variability is retained in extreme events.…”
Section: Climate Emulator Twl Outputsupporting
confidence: 86%
See 1 more Smart Citation
“…The direct simulation of extreme compound TWL events also allows for a greater investigation of the respective constitutive components. Similar to the findings of Serafin et al (), Figure demonstrates how annual maxima can occur across a broad range of values within each TWL component. Identifying the 1% recurrence events (red dots in Figure , defined as the fifth largest event in each simulation) reveals the degree to which this variability is retained in extreme events.…”
Section: Climate Emulator Twl Outputsupporting
confidence: 86%
“…While most of the 1% recurrence events occur when wave heights are greater than 5 m and wave periods longer than 15 s, there is an infinite combination of univariate drivers that can combine to generate compound extreme events—even for a simple TWL proxy such as equation . Such different TWL components can lead to different impacts on the open beach (Cohn et al, ; Serafin et al, ; Serafin et al, ) and different flood extents in the backshore (Bilskie & Hagen, ). The presented framework can be a tool used to make informed decisions for the input conditions to dynamical numerical modeling studies assessing flood extents and hazard zones contingent on future extremes (Barnard et al, ; Erikson et al, ).…”
Section: Climate Emulator Twl Outputmentioning
confidence: 99%
“…Wave run-up (and therefore swash excursion) is a key component used to evaluate inundation hazards and vulnerability to storm impacts (e.g. Bosom and Jiménez, 2011;Stockdon et al, 2007;Serafin et al, 2017). Stockdon et al (2007) found that the wave action counted for about 48 % of the maximum total water level during two hurricanes along the USA coast.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we expect uncertainties in the water surface elevation imposed at the downstream boundary of the hydraulic model domain to strongly influence extreme water levels in the downstream reach. Wave contributions, such as wave setup and wave propagation, are also not directly represented by the BN but can strongly influence water levels [88][89][90]. While this study can be improved by using complementary data at these stations, this typically requires dedicated and extensive studies to properly capture complex coastal and hydrological processes [64,91,92] and is left for future studies.…”
Section: Discussionmentioning
confidence: 99%